Careers : thinking, strategising and prototyping - Brewer, Ann M. (Emerald Publishing Limited, 2020)
Considering career development in the current and future work landscape, this book explores a leading-edge framework for careers, drawing on design thinking to apply career planning to a wide range of individual contexts. The book encompasses diverse stakeholders at various stages of the career process, including career seekers, employers, trainers and educators to demonstrate the creation and flow of value for effective careers in a fast-moving and dynamically altering labour market. Using a design thinking framework, Ann M. Brewer presents compelling evidence of the need for career strategising to assist all workers in achieving their career aspirations and goals. This hands-on approach addresses the emotional and cognitive investment of career thinking and planning from an early career stage to a late career stage perspective, while the key emphasis on prototyping provides an opportunity to change the way careers are created. This far-reaching, well-rounded, highly creative, solutions-oriented framework is a useful resource for professionals and students considering future career progression within any work context, and researchers of employability, career management and career thinking.
Part I: Thinking careers -- Chapter 1: What is a career in the 21st century? -- Chapter 2: Career thinking competence -- Part II: Strategising careers -- Chapter 3: Career strategising -- Chapter 4: Design thinking a career -- Part III: Prototyping careers -- Chapter 5: Career prototyping: designing career through a self-narrative -- Chapter 6: Careers and corporate social responsibility: Questions and a concluding note.
Includes index.
Print version record.
Keywords: Career development; Social responsibility of business; Business & Economics, Careers -- General; Research & development management